2013
DOI: 10.1039/c3ay41149d
|View full text |Cite
|
Sign up to set email alerts
|

Direct mass spectrometry analysis of untreated samples of ultralow amounts using extraction nano-electrospray

Abstract: Direct mass spectrometry analysis of untreated samples of volumes as low as 0.2 µL were achieved using fast extraction and nanoESI (electrospray ionization) in a combined fashion. The analytes in dried samples on paper substrates were extracted by organic solvent in a nanoESI tube and ionized with a high voltage applied for generating a spray. The ionization source produced stable signals for different atmospheric pressure interfaces of triple quadrupole instruments. Analysis time more than 20 minutes were ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Some examples include the detection of chemical warfare agents at low ppb levels using direct analysis in real time [37], 0.62 pg/ml nicotine in gas phase samples using extractive ESI [38], 100 fmol of peptides using electrospray-assisted laser desorption ionization [39], and 0.2–40 ng drug molecules in plasma using DESI [40]. Using the extraction nano-ESI method developed recently, LODs as low as 0.1 ng/ml were obtained for therapeutic or illicit drug compounds in blood, with an amount of sample consumed as low as 0.2 μl [41]. If these kinds of sensitivities along with the low amounts of sample required can be transferred into analysis for clinical diagnosis, it means mandatory sensitivities might be achieved using minimally invasive methods for sampling, such as a finger prick instead of a venous blood draw.…”
Section: Adequate Sensitivity Without Extensive Purificationmentioning
confidence: 99%
“…Some examples include the detection of chemical warfare agents at low ppb levels using direct analysis in real time [37], 0.62 pg/ml nicotine in gas phase samples using extractive ESI [38], 100 fmol of peptides using electrospray-assisted laser desorption ionization [39], and 0.2–40 ng drug molecules in plasma using DESI [40]. Using the extraction nano-ESI method developed recently, LODs as low as 0.1 ng/ml were obtained for therapeutic or illicit drug compounds in blood, with an amount of sample consumed as low as 0.2 μl [41]. If these kinds of sensitivities along with the low amounts of sample required can be transferred into analysis for clinical diagnosis, it means mandatory sensitivities might be achieved using minimally invasive methods for sampling, such as a finger prick instead of a venous blood draw.…”
Section: Adequate Sensitivity Without Extensive Purificationmentioning
confidence: 99%
“…Researchers are insistently looking for a tradeoff between performance and convenience. Ren et al reported micro-extraction nano-ESI ionization methods for the one-step analysis of paper-based [33] and liquid-phase [34] samples, in which the extraction process with a trace sample was executed in a nano-ESI tube taking advantage of the high performance of the nano-ESI. Nevertheless, the drawbacks associated with the glass tube nano-ESI were not avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Sample processing can be minimized for analysis of complex samples using an effective ambient ionization method[2]. Some successful applications have also been demonstrated by Laser ablation electrospray ionization,[10] electrochemical electrospray ionization[11], coated blade spray[12,13], electrospray-assisted laser desorption ionization[14], paper spray[15] and extraction spray[16]. These achievements suggest a promising direction in technical development for direct MS analysis of complex samples.…”
Section: Introductionmentioning
confidence: 99%